Kirk-Othmer Encyclopedia of Chemical Technology 2007
DOI: 10.1002/0471238961.ionisedd.a01
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids

Abstract: This article deals with the literature on ionic liquids, with the focus on nomenclature, preparation, and handling of the second‐generation ionic liquids. In the older (and some current) literature, ionic liquids are sometimes called liquid organic salts, fused salts, molten salts, ionic melts, NAILs (nonaqueous ionic liquids), room‐temperature ionic liquids, OILs (organic ionic liquids) and ionic fluids. Their most prominent feature, namely the potential of tuning their physical properties to suit a particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 443 publications
0
53
0
Order By: Relevance
“…[231] With a rational combination of different templates, such as polymer colloid, block copolymer micelle, and ionic liquid micelle, it was possible to fabricate trimodal hierarchical porous materials. [232] Smarsly and co-workers found that the use of PS spheres led to the formation of macropores (360 nm), and the macroporous walls were composed of large spherical mesopores (12 [233] It seems that the formation of these types of trimodal porous SiO 2 materials using ionic liquids is still challenging, and the compatibility of these three types of templates is important for successful preparation. More experiments are needed to understand the compatibility of different templates.…”
Section: Hierarchical Porous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[231] With a rational combination of different templates, such as polymer colloid, block copolymer micelle, and ionic liquid micelle, it was possible to fabricate trimodal hierarchical porous materials. [232] Smarsly and co-workers found that the use of PS spheres led to the formation of macropores (360 nm), and the macroporous walls were composed of large spherical mesopores (12 [233] It seems that the formation of these types of trimodal porous SiO 2 materials using ionic liquids is still challenging, and the compatibility of these three types of templates is important for successful preparation. More experiments are needed to understand the compatibility of different templates.…”
Section: Hierarchical Porous Materialsmentioning
confidence: 99%
“…However, only a few typical ionic liquids ( Fig. 1), [12,13] especially those containing imidazolium cations, [14] are commonly used at the moment. Significant attention has been paid to the application of ionic liquids as neoteric media for extraction, organic synthesis, REVIEW www.advmat.de biphasic catalysis, and materials synthesis, [13,[15][16][17][18][19][20][21] as witnessed by the emergence of thousands of publications in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…• C. 4,6,14,17 The fully-converted RevIL had a conductivity of 0.0020 ± 0.0002 mS/cm, but was not experimentally different than the ML. This shows that the RevIL in its pure state is essentially non-conductive.…”
Section: Resultsmentioning
confidence: 99%
“…• C. 4,6,14,17 EWs can be 5-6 V and greater 18 (compared to the theoretic window for water of 1.2 V). Highly viscous ILs and ILs with strongly-associated ions have lower conductivities than other ILs.…”
mentioning
confidence: 97%
See 1 more Smart Citation